Adults with autism spectrum disorder are sensitive to the kinematic features defining natural human motion. Issue 2 (21st December 2018) - Edey, Rosanna; Cook, Jennifer; Brewer, Rebecca; Bird, Geoffrey; Press, Clare
Abstract : It has been hypothesized that individuals with Autism Spectrum Disorder (hereafter "autism") have problems perceiving biological motion, which contributes to their social difficulties. However, the ability to perceive the kinematic profile characteristic of biological motion has not been systematically examined in autism. To examine this basic perceptual ability we conducted two experiments comparing adults with autism with matched typical adults. In Experiment 1, participants indicated whether two movements—which differed in the quantity of formula‐generated biological motion—were the same or different. In Experiment 2, they judged which of two movements was "less natural, " where the stimuli varied in the degree to which they were a product of real movement data produced by autistic and typical models. There were no group differences in perceptual sensitivity in either experiment, with null effects supported by Bayesian analyses. The findings from these two experiments demonstrate that adults with autism are sensitive to the kinematic information defining biological motion to a typical degree—they are both able to detect the perceptual information in a same‐different judgment, and as inclined to categorize biological motion derived from real models as natural. These findings therefore provide evidence against the hypothesis that individuals with autism exhibit low‐level difficulties in perceiving the kinematics of others' actions, suggesting that atypicalities arise either when integrating this kinematic information with other perceptual input, or in the interpretation of kinematic information. Autism Res 2019, 12: 284–294 © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: It has previously been suggested that autistic children and adults have problems perceiving the detailed manner in which others move—that is, the subtle changes in speed as we move from point to point—which may impact on their ability to learn from, and about, others in a typical fashion. However, the results from the present two studies demonstrate that adults with autism can perceive this information, suggesting that atypicalities in processing others' movement may arise mainly as a consequence of atypical interpretation rather than perception.